Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.10.26.20219089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated Single-Cell Atlases Reveal an Oral SARS-CoV-2 Infection and Transmission Axis

Abstract: Despite signs of infection, the involvement of the oral cavity in COVID-19 is poorly understood. To address this, single-cell RNA sequencing datasets were integrated from human minor salivary glands and gingiva to identify 11 epithelial, 7 mesenchymal, and 15 immune cell clusters. Analysis of SARS-CoV-2 viral entry factor expression showed enrichment in epithelia including the ducts and acini of the salivary glands and the suprabasal cells of the mucosae. COVID-19 autopsy tissues confirmed in vivo SARS CoV-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 72 publications
0
65
0
Order By: Relevance
“…Several viruses, including poxviruses, papillomaviruses, herpesviruses, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; Huang et al., 2020 ), invade via and replicate in the oral epithelium. Thus, it is of medical importance to better understand tissue surveillance within the oral mucosa.…”
Section: Main Textmentioning
confidence: 99%
“…Several viruses, including poxviruses, papillomaviruses, herpesviruses, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; Huang et al., 2020 ), invade via and replicate in the oral epithelium. Thus, it is of medical importance to better understand tissue surveillance within the oral mucosa.…”
Section: Main Textmentioning
confidence: 99%
“…A very recent study revealed that SARS-CoV-2 multiplies robustly in the oral cavity, and this likely explains why patients with COVID-19 express a range of oral manifestations such as ageusia and oral blisters. 51 In summary, the following points are noted: (1) infectivity is higher immediately before and soon after the onset of symptoms; however infected patients can remain infectious for about 2 weeks; (2) ten days from the appearance of the initial symptoms, the risk that a patient is still infections varies between 1% to 10% at a 95% CI; (3) infectivity is related to the viral load, but not to the development and severity of COVID-19; (4) individuals with a low viral load, determined by Ct greater than or equal to 35, may be infectious; (5) the window of infectivity varies in different individuals and some may be infectious for several weeks (these "long-term spreaders" represent a fraction of the infected population, probably too small to significantly affect the spreading of the virus; thus, the quarantine length could ignore them. At lower levels of virus circulation, however, long-term spreaders may frustrate efforts to further curb the epidemic if the quarantine length is not long enough to account for their prolonged infectivity window); and (6) most importantly, asymptomatic individuals-who account for about 70% of infectionsseem able to spread the virus as well as those who become ill 50 ; if this is true, it will be much more difficult to contain the further spread of this pandemic.…”
Section: Viral Infection Routes Of Transmission and Window Of Infecmentioning
confidence: 99%
“…The transmembrane protein receptor ACE2 (angiotensin 2 converting enzyme), as well as TMPRSS2 (transmembrane serine 2 protease) and furin enzymes, have been identified as critical determinants of oral SARS infectivity [ 189 ]. ACE2 is expressed on different cells of oral tissues including oral mucosa, gingiva, tongue, salivary glands, and tonsils [ 49 , 190 , 191 , 192 , 193 , 194 , 195 , 196 ] ( Figure 1 ). Almost 96% of ACE2-positive oral cells would locate in dorsal tongue.…”
Section: Sars-cov-2 Transmission and Oral Cavitymentioning
confidence: 99%
“…The presence of ACE2 is confirmed in the taste epithelial cells of tongue fungiform papillae. The epithelial cells of salivary ducts and serous cells of human submandibular glands express abundantly ACE2 [ 191 , 195 , 196 ]. Its expression in epithelial cells of minor salivary glands is even higher than in lung cells, and could constitute a reservoir zone for SARS-CoV-2 in asymptomatic patients [ 193 , 196 ].…”
Section: Sars-cov-2 Transmission and Oral Cavitymentioning
confidence: 99%